How Phytohormones Synthesized by PGPR Affect Plant Growth? - Vieira Stefen D.L. (2022)
© The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2022.Plant growth-promoting rhizobacteria (PGPR) are important microorganisms that can induce the secretion of phytohormones, like auxins, gibberellic acid, abscisic acid, cytokinins, and ethylene, and play an important role in plant growth. Plant growth benefits due to the addition of PGPR include increases in germination rate, root growth, yield, crop quality, leaf area, chlorophyll, nitrogen, protein content, tolerance to stresses, shoot and root weight, delayed leaf senescence, and tolerance to pests and diseases. PGPR confers tolerance to plants under stressful environments promoting their growth. Then, the possible explanation for the mechanism of biotic and abiotic stress tolerance includes the production of phytohormones. In this chapter, we present the benefits that phytohormones produced by PGPR bring to plants, indicating that the use of PGPR becomes an appropriate strategy and a trend in the sustainable development of plants under environmental stresses.